Forensic analysis of pepper sprays by chromatographic technique - Ali, Noor Yasmin Mohamad (2023)
Pepper sprays have gained popularity as personal defence tools due to their ease of production and accessibility of ingredients at home, as well as readily availability in the market. Their potential use in criminal activities necessitates effective forensic analysis methods to accurately identify and differentiate the chemical constituents present. Therefore, this study was aimed to evaluate the chemical profiles of homemade and commercially available pepper sprays in Malaysia by gas chromatography-mass spectrometry (GC-MS). In this study, five homemade pepper sprays made up of different species of chilli pepper, namely red and green chilli, red and green bird’s eye, and habanero pepper, as well as four commercial pepper sprays were investigated. Both homemade and commercial pepper spray samples underwent sample preparation step to extract the active compounds from the samples and analysed using gas GC-MS followed by principal component analysis (PCA). From the study, a GC-MS method was optimised for the analysis of pepper spray samples. Capsaicin and dihydrocapsaicin were found to be present in all homemade pepper spray samples. Additional peaks corresponding to homocapsaicin, homodihydrocapsaicin, and nonivamide were also observed in green and red bird's eye-, as well as habanero-prepared pepper spray solutions. Moreover, pepper spray solutions produced from red bird's eye and habanero exhibited extra peak corresponding to nordihydrocapsaicin. In contrast, the commercial pepper spray only contains one capsaicinoid compound, namely nonivamide. The PCA allowed for the differentiation of homemade and commercially available pepper sprays by considering only the capsaicinoid contents. Further discrimination, especially among the homemade samples could be achieved by decomposing the 74 interpretable peaks from the GC-MS profiles. To conclude, the chemical composition of pepper sprays, especially the handmade and commercially available pepper sprays were determined through the GC-MS method. It would be used to analyse any forensic evidence suspected to have contained pepper spray residues to link to the possible sources.